A bi-level and robust optimization-based framework for a hazardous waste management problem: A real-world application. (10th April 2020) - Saeidi-Mobarakeh, Zahra; Tavakkoli-Moghaddam, Reza; Navabakhsh, Mehrzad; Amoozad-Khalili, Hossein
Abstract: Hazardous waste management is a hierarchical process. In the upper level of the hierarchy, the government's policies on planning and controlling the waste management infrastructure aim to overcome the environmental concerns related to the disposal of waste materials. On the other hand, the follower of the hierarchical process decides about waste collection plans considering the government-approved infrastructure to minimize total operational costs. From this point of view, the present study proposes a bi-level mathematical formulation to model the problem of hazardous waste management. Also, to tackle the highly fluctuating nature of hazardous waste generation rates, our study addresses the most probable, optimistic and pessimistic scenarios of this key parameter. To solve the problem under uncertainty, a multi-part solution methodology combining the robust optimization approach, a method of reformulating the bi-level model into Mixed-Integer Linear Programming (MILP) formulation as well as a feasibility repairing mechanism is applied. In the end, the model and the solution methodology are illustrated with a real-life hazardous medical waste management problem and practical insights are derived. Graphical abstract: Scheme of a hazardous waste location-routing problem in the presence of two stakeholders. Image 1 Highlights: Developing a bi-level optimization model to support hazardous waste management. Addressing the network design and waste collection problems in the decision-making hierarchy. Implementing a three-part solution methodology using mathematical programming methods. Developing a robust optimization approach to cope with the uncertainty of the waste generation rates. Illustrating a real-world case study as the application of the proposed methodology.